Word to the World the collected writings of Wiliam S. Barker - Barker, William S. (Fearn, Ross-shire Mentor, 2005)
The church is suffering from crises in identity, belief and government involvement - they are all connected. The reason the church has problems interacting with government is because it doesn't understand its mission, history and authority.
Keywords: Hodge, Charles, -- 1797-1878. Westminster Confession of Faith. Hemphill, Samuel, -- -1741.